Extract of seaweed Gracilaria verrucosa as immunostimulant to controlling white spot disease in Pacific white shrimp Litopenaeus vannamei - Aminatul Zahra; Sukenda Sukenda; Dinamella Wahjuningrum (Jurnal Akuakultur Indonesia)
ABSTRACT